Fostering critical thinking in the classroom - Sahamid, Husniah (Australian International Academic Centre, 2014)
The ability to cite reasons, to justify claims and give support to arguments is seen as primary characteristics of a critical thinker. This paper discusses how the ‘Elements of Reasoning’ is employed with Socratic Questioning to develop critical thinking in the language classroom. The principles that guide the questioning are laid out clearly, just as is the response which must be backed by valid reasons, examples, and illustrations, pushing students beyond mere recall and into abstract thinking. It is based on the notion that through questioning, the process that occurs in the student’s mind creates thinking and learning.